Feasibility Analysis of Transport Demand Management Policies through a Bottom-Up Planning Approach - Ali Soltani; Andrew Allan (International Journal of Advances in Applied Sciences, 2012)
In order to reduce traffic congestion and the associated problems, various policies have been put forward so far. In this way, it is believed that Transport Demand Management (TDM) offers an effective and economical solution. Since most TDM policies have both positive and negative impacts, public participation is, therefore, an efficient way to achieve better results. This paper attempts to evaluate a set of TDM policies and define their priorities through a Bottom-up Planning (BUP) approach for the metropolitan Shiraz, Iran. In this way, the possibility of developing common principles via the investigation of shared goals within an integrated framework for urban transport policies that are desired for sustainable transport is evaluated. The framework method was utilized through a BUP expert consultation process. A number of experts (n=21) were asked to prioritize the components of each policy package. A set of policy measures as solutions to traffic congestion was provided in three different categories: sustainable transport approach, engineering approach, and traffic restraint approach. Each category included 10 measures which were suggested after a primary survey on the metropolitan's traffic problems. These measures were weighted and rated using the Analytical Hierarchal Process (AHP) technique. Then the Weighted Scoring Method was applied to find performance priorities. Public bus and bicycle infrastructure development were found to be the two most favorite policies. In total, sustainable transport solutions were the most preferred policies in the bottom-up stages. The findings can contribute some insights to future transport planning in order to provide more opportunities for community involvement in planning processes.